Performance of toughened acrylic thermoplastic composites under mode I loading - Ng, Ronald Zi Foong (Nanyang Technological University, 2023)
The development of advanced material systems, such as composites, has gained popularity due to their remarkable mechanical features, including excellent strength and stiffness relative to weight. While composites are made up of a combination of two materials, a matrix system and reinforcement, advancements in polymer research have led to the development of Elium®, an innovative thermoplastic acrylic resin that cures at room temperature.